Vacuum Impregnation: Emerging Technology for Osmotic Dehydration and Value Addition in Fruits and Vegetables - Verma , Vikash Chandra (Journal of Postharvest Technology, 2024)
There is a great attention in recent years to develop an effective method for preservation of fruits and vegetables. Osmotic dehydration being simple process involves dehydration of fruits along with the retention of its aroma colour and nutritional compounds. Vacuum environment may be used to increase the rate of mass transfer. Vacuum Impregnation is emerging technology for osmotic dehydration having high rate of mass transfer due to the action of hydrodynamic mechanism promoted by pressure changes. It is a technique for introducing external liquids in void phase of foods sample in a controlled manner. It may be used to introduce several compounds to prolong shelf life, to enrich fresh food with nutritional and/or functional substances, to obtain innovative food formulations as pre-treatments before drying or freezing, etc. Anti-browning agents, firming agents, nutritional compounds, functional ingredients, antimicrobial agents, anti-freezing, enzymes, etc. serves the purposes. It is a useful technique to fill the void phase of foods with nutritional and functional ingredients. So the possibility to obtain foods with high nutritional and functional properties exponentially increases with this emerging technology. It was found to be a useful method to incorporate in void phase of foods cryoprotectants and cryostabilizers, such as hypertonic sugar solution, antifreeze protein (AFP), high methoxyl pectin, etc. which decreases the drip loss during thawing. One major issue is the large-scale industrial application of VI and other is the management of the remained solution at the end of the process. Other approaches need to be considered and requires a substantial research.